Bond behavior of steel fibers reinforced self-stressing and self-compacting concrete filled steel tube columns. (15th January 2018) - Lu, Yiyan; Liu, Zhenzhen; Li, Shan; Li, Na
Highlights: Push-out tests on steel fibers reinforced self-compacting self-stressing CFST. Self-stress significantly improves the bond strength of CFST specimens. Steel fibers firstly decrease and then increase the bond strength of CFST specimens. Predicted formulas for the bond strength of FSSCFST specimens are proposed. Abstract: This paper investigates the bond behavior of steel fibers reinforced self-stressing and self-compacting concrete filled steel tube (FSSCFST) columns. A series of push-out tests on ninety CFST columns are conducted. The variables considered in the test are: (a) concrete type (self-compacting concrete and steel fibers reinforced self-stressing self-compacting concrete); (b) the thickness of steel tube (2.5–4.25 mm); (c) concrete strength (C40, C50 and C60); and (d) steel fibers volume percentage (0%, 0.6% and 1.2%). Experimental results show that the bond strength of FSSCFST specimens varies from 0.50 MPa to 2.51 MPa, which is generally higher than the self-compacting CFST specimens. Self-stress significantly improves the bond strength of CFST specimens, and the average improvement level is 42.7%. The bond strength firstly decreases and then increases with the increase of steel fiber volume percentage. Finally, formulas are proposed to predict the bond strength of FSSCFST columns, and the proposed formulas give a more accurate prediction than the existing design codes.